Heavy metals in freshwater snails of Kuala Klawang's rice field, Negeri Sembilan, Malaysia - Ismail, A. (Kluwer Academic Publishers, 1994)
A study of heavy metal contents in freshwater snails from rice fields have been made. The results indicate that the levels of heavy metals, Pb, Cu, Zn and Cd, are low and within the permissible limit of Malaysian Food Regulations. The results can serve as background data for further reference.